The Effect of Corrective and Aerobic Exercises on General Health Index, Body Composition of Women with Postural Hyperkyphosis - Mohadeseh Golzar Janat; Arsalan Damirchi; Ali Shamsi Majelan (مجله علوم پزشکی صدرا, 2025)
Introduction: Age-related muscle weakness contributes to an increased prevalence of postural abnormalities, such as hyperkyphosis, which adversely affects body composition, mental health, and overall quality of life. This study aimed to investigate the effects of corrective and aerobic exercises on the general health index and body composition in women with postural hyperkyphosis.Methods: Thirty-two women with a kyphosis angle exceeding 40 degrees were purposefully selected and randomly assigned to four groups (n=8 per group): control, aerobic exercise, corrective exercise, and combined aerobic-corrective exercise. The intervention consisted of six weeks of structured aerobic and corrective exercises (including stretching, mobility, and strength training). Kyphosis angle, general health (assessed via the GHQ questionnaire), and body composition parameters (weight, body mass index [BMI], fat percentage, visceral fat, and muscle mass) were measured pre-and post-intervention. The dependent t-tests were used to compare within-group changes, while ANCOVA was employed to assess the exercise effect after controlling for baseline values. All statistical analyses were performed using SPSS software (version 23) at a significance level of P≤0.05.Results: Corrective, aerobic, and combined exercises significantly improved the general health index (P≤0.05), with the greatest effect observed in the combined exercise group. However, none of the interventions significantly altered body composition measures (visceral fat, muscle mass, fat percentage, BMI, or body weight; P≥0.05).Conclusion: The findings suggested that the corrective and aerobic exercises, particularly when combined, were effective for enhancing general health and reducing kyphosis angle in women with postural hyperkyphosis; however, they do not significantly impact body composition.